det er noget kastrert ved den ...": Sigrid Undsets oppgjør med protestantismen - Oftestad, Bernt T. (Norsk teologisk tidsskrift, 2006)
In 1924 Sigrid Undset converted to the Catholic Church. The following years she devoted herself to the defense of the Catholic faith and critics of contemporary Protestantism. The discussion between Undset and Norwegian Lutheran theologians was especially concentrated on the Reformation. She rejected the Lutheran principle of Sola Scriptura, because of its intellectualizing effects on the concept of faith. In the twenties liberal Protestantism was still an important theological stream in Norway. Undset attacked its individualism and subjectivism, as a Catholic she opposed liberal theology because of its dissolution of dogma.